Revisión de los modelos de producción de voz después de una laringectomía total: opciones de calidad de voz - Fernández Baillo, Roberto (Revista de Investigación en Logopedia, 2011)
The laryngectomized patient is one who because of a carcinogenic process has undergone surgery which results in complete removal of the larynx. Following this operation the patient undergoes a series of anatomical changes that involve the alteration and/or loss of certain functions, being the voice loss, and the oral communication, the main problem faced by the patients. Therefore, the restoration of the oral communication is one of the main objectives in the treatment process and post-surgical rehabilitation. This should give the patient a new sound source, which will have to replace or emulate the function of the laryngeal glottis. The objective of this work is to analyze from a biomechanical and acoustic perspective the different types of voices that can postulated as an option for laryngectomized patients. We show the advantages and limitations of each model of production, in a clear, objective and understandable way for both clinicians and patients, to guide the decision-making. Finally, an analysis of the voice sound of four female laryngectomized patients is carried out. Each voice sample corresponds to a different voice production model: artificial larynx, phonatory prosthesis and erygmophony. The results provide an objective assessment of the acoustic characteristics of each voice.
Keywords: Acoustic Analysis; Cancer of Larynx; Dysphonia; Erygmophony; Esophageal Voice.